Delegation and Information Revelation - Axel Gautier; Dimitri Paolini (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
This paper addresses the question of delegation in a partial contracting set-up, where only the control over actions is contractible. We consider an organization that should take two decisions, affected by a common state of the world parameter only known by the agent. We show that, if the principal gives up the control over the first decision, to the better informed agent, the decision of the agent signals his private information to the principal. The revelation of information, associated with delegation, is valuable for the principal if she retains control over the second decision. Hence, this paper provides a new rational for partial delegation: a transfer of control to the better-informed party can be used by the supervisor to elicit the agent's private information. We establish this result by using the properties of signalling game. Finally, we show that, even if there are loss of control associated with delegation, the benefits of information revelation outweighs these costs and delegation could dominate centralization of all decisions by the principal, even in the case where she uses messages from the agent to acquire information; because those messages could be noisy.
Keywords: L22; D82; D23; 330; Delegation; Asymmetric information; Transferable control action; Signalling game; Spieltheorie; Signalling; Agency Theory; Vertragstheorie; Asymmetrische Information; Theorie